CF / Cu2S (at) MoS2 heterojunction surface-enhanced Raman scattering sensing substrate as well as preparation method and application thereof

By forming a CF/Cu2S@MoS2 heterojunction structure on the copper foam substrate, the problem that traditional detection technology cannot accurately identify microplastics and nanoplastics is solved, and efficient and accurate detection effects are achieved, with the detection limit reaching 50μg/mL and 10 -8M.

CN119269393AActive Publication Date: 2025-01-07HEFEI UNIV OF TECH

Patent Information

Application Number
CN202411413499.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-07
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Traditional detection technologies are unable to accurately identify and quantify microplastics and nanoplastics, resulting in an urgent need for more efficient and accurate detection methods in the fields of environmental science and public health.

Method used

The Raman scattering sensing substrate is enhanced by using CF/Cu2S@MoS2 heterojunction surface, and the Cu(OH)2 nanorod array is grown in situ on the copper foam substrate, and the Cu2S nanorod array is formed by hydrothermal vulcanization, and then in the MoS2 is grown on it, forming a core-shell heterostructure, and enhancing the Raman scattering signal.

Benefits of technology

The detection accuracy and sensitivity of microplastics and nanoplastics are significantly improved, and the concentration of polystyrene particles can be detected to reach 50μg/mL, the minimum detection concentration of methylene blue reaches 10-8M, and the substrate surface uniformity and stability are good.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269393A_ABST
    Figure CN119269393A_ABST
Patent Text Reader

Abstract

The invention discloses a CF / Cu2S (at) MoS2 heterojunction surface-enhanced Raman scattering sensing substrate and a preparation method and application thereof, and relates to the technical field of micro-plastics and nano-plastics, and the preparation method comprises the following steps: cleaning a CF (copper foam) substrate, immersing the cleaned CF substrate in a precursor solution for a reaction, and after the reaction, washing the treated CF substrate to obtain a CF / Cu (OH) 2 composite material; step 2, dissolving Na2S. 9H2O in deionized water, carrying out ultrasonic treatment to obtain a clear solution, then adding the CF / Cu (OH) 2 composite material obtained in the step 1 into the clear solution, transferring into a high-pressure reactor, and washing and drying after the reaction is completed to obtain a CF / Cu2S composite material; and step 3, preparing a mixed solution, immersing the CF / Cu2S composite material obtained in the step 2 into the mixed solution for heat treatment, and after heat treatment, washing and drying to obtain the CF / Cu2S-coated MoS2 composite material. The detection limit of the CF / Cu2S (at) MoS2 heterojunction surface enhanced Raman scattering sensing substrate on PS particles reaches 50 [mu] g / mL, and the substrate shows very strong linear correlation (R2 = 0.98).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of microplastics and nanoplastics, and in particular to a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate and its preparation method and application. Background Art

[0002] As an emerging environmental pollutant, plastic particles pose a potential threat to ecosystems and human health due to their unique physical and chemical properties. They are widely distributed in the environment and are almost ubiquitous, from the deep sea to the mountains, from the poles to the equator. Environmental factors, including geochemical, photochemical and biological processes, drive the degradation of plastic waste in terrestrial and marine environments, resulting in particles of various sizes: macroplastics (mP, larger than 5 mm), microplastics (μP, 1 μm to 5 mm) and nanoplastics (nP, 1 to 1000 nm). They have extremely high adsorption capacity and can capture harmful pollutants from aquatic environments, which then enter biological systems through food webs, posing a growing risk to ecosystems and human health. Nanoplastics, due to their tiny size, easily cross biological barriers and penetrate into tissues. Such phenomena may cause a series of health problems, including inflammation, tissue damage and vascular occlusion. However, traditional detection technologies are often unable to accurately identify and quantify these tiny plastic particles. This limitation highlights the urgent need to develop more efficient and accurate nanoplastic detection methods in the fields of environmental science and public health.

[0003] Patent document [CN 108950585] discloses a MoS2@Cu2S@foam copper composite nanomaterial, which is used in the field of electrolytic water catalytic hydrogen evolution technology. However, its surface is rough and its structure is uneven, which obviously cannot be used in the field of microplastics and nanoplastics technology. Therefore, this application proposes a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate for the field of microplastics and nanoplastics technology. Summary of the invention

[0004] The purpose of the present application is to provide a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate for use in the fields of microplastic technology and nanotechnology.

[0005] The present application provides a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate. The preparation method of the CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate is as follows:

[0006] Step 1: After cleaning the CF substrate, immerse it in a precursor solution for reaction. After the reaction, rinse the treated CF substrate to obtain a CF / Cu(OH)2 composite material;

[0007] Step 2, dissolving Na2S·9H2O in deionized water, performing ultrasonic treatment to obtain a clear solution, then adding the CF / Cu(OH)2 composite material obtained in step 1 to the clear solution, transferring the solution to a high-pressure reactor, and after the reaction is completed, washing and drying to obtain a CF / Cu2S composite material;

[0008] Step 3: prepare a mixed solution, immerse the CF / Cu2S composite material obtained in step 2 into the mixed solution for heat treatment, wash and dry to obtain the CF / Cu2S@MoS2 composite material after the heat treatment.

[0009] Preferably, in step one, the process of cleaning the CF substrate is to use HCl, deionized water and anhydrous ethanol to clean it in sequence, and the precursor solution is a mixed solution of NaOH solution and (NH4)2S2O8 solution.

[0010] Preferably, in step three, the mixed solution is prepared by dissolving Na2MoO4·2H2O and (NH2)2CS in deionized water, followed by ultrasonic treatment to obtain a mixed solution.

[0011] Preferably, in step three, the specific step of heat treatment is that the CF / Cu2S composite material obtained in step two is immersed in the mixed solution and placed in an oven at 180°C for heat treatment for 22 hours.

[0012] The present application provides a heterojunction surface enhanced Raman scattering sensing substrate obtained by the preparation method of the above-mentioned CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate.

[0013] The present application provides an application of a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate in microplastics and nanoplastics.

[0014] Preferably, the detection concentration of the CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate for polystyrene particles is at least 50 μg / mL, and the minimum detection concentration for methylene blue is 10 -8 M.

[0015] Therefore, the present application adopts the above-mentioned CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate, which has the following beneficial effects:

[0016] 1. High-density Cu(OH)2 nanorod arrays were grown in situ on the CF surface by alkaline etching. Subsequently, the Cu(OH)2 precursor was sulfided by a hydrothermal method to obtain copper sulfide nanorod arrays. Finally, MoS2 was grown directly on the Cu2S nanorods using an in situ growth strategy to form CF / Cu2S@MoS2 nanorod arrays with a core-shell heterostructure. This vertical growth of Cu2S@MoS2 nanorod arrays and the carefully designed core-shell heterostructure not only enhance mass transport but also ensure efficient electron transfer to active sites.

[0017] 2. Copper foam has high porosity, conductivity, unique 3D structure and mechanical stability.

[0018] 3. Cu2S is a p-type semiconductor with a band gap of 1.2eV. Its unique electronic structure gives it significant potential in SERS applications. The high density of vacancies in Cu2S (approximately 10 21 cm -3 ) leads to a significant surface plasmon resonance (SPR) effect, especially in the near-infrared region. At the same time, the integration of n-type semiconductor MoS2 forms a built-in electric field, which significantly improves the charge transfer (CT) efficiency, thereby greatly enhancing the SERS activity. By utilizing semiconductor heterojunction technology, we can take advantage of the unique properties of various materials to generate a large number of separable electron-hole pairs, thereby effectively expanding the photoresponse spectrum of the pn heterojunction. At the heterojunction interface, the band bending and the generation of internal electric field (IEF) significantly increase the speed of carrier separation and transmission, thus providing a key advantage for optimizing SERS. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The SEM images of Cu foam, CF / Cu(OH)2, Cu2S, Cu2S@MoS2 and the schematic diagram of the preparation of CF / Cu2S@MoS2 nanorod arrays, where (a) is the schematic diagram of the preparation of CF / Cu2S@MoS2 nanorod arrays; (b) is the SEM image of Cu foam; (c) is the SEM image of CF / Cu(OH)2; (d) is the SEM image of CF / Cu2S; (e) is the SEM image of CF / Cu2S@MoS2;

[0020] Figure 2(ab) TEM images, element distribution and Raman spectra of Cu2S@MoS2; (a) and (b) are TEM images of CF / Cu2S@MoS2, (c) is a high-resolution TEM image of CF / Cu2S@MoS2 (insertion of SAED pattern); (d), (e), (f) and (g) are the element mapping distributions of the capping layer, Cu, S and Mo, respectively; (h) is the XRD pattern of Cu2S, Cu2S@MoS2 and MoS2; (i) is the XRD pattern Raman spectrum of Cu2S, Cu2S@MoS2 and MoS2; (j) is the Mo 3d XPS spectrum of Cu2S@MoS2;

[0021] Figure 3 SEM micrographs (ad) at different reaction times and reaction temperatures; (a), (b), (c), (d) are SEM images at different reaction times; (e), (f), (g), (h) are SEM images at different reaction temperatures; SERS performance at different times (i) and comparative bar graph (j); SERS performance at different temperatures (k) and comparative bar graph (l);

[0022] Figure 4 In the figure, (a) is the SERS spectra of MB with different concentrations adsorbed on CF / Cu2S@MoS2 nanorod arrays; (b) is the SERS spectra at 1617 cm -1 The linear correlation between the Raman intensity at 1000 nm and the logarithm of the MB concentration; (c) is the temporal variation of the SERS spectrum of the CF / Cu2S@MoS2 nanorod array substrate; (d) is the logarithm of the MB concentration adsorbed on the CF / Cu2S@MoS2 nanorod array substrate recorded at 25 different points. -5 SERS spectra of MB of M, and 1617 cm -1 The corresponding RSD values ​​of the peak; (e) are the values ​​of 1617cm -1 RSD values ​​of the peaks; (f) SERS measurements of random points from different batches (RSD1 = 10.5%, RSD2 = 10.3%, RSD3 = 10.7%, RSD4 = 10.6% RSD5 = 10.5%);

[0023] Figure 5 In the figure, (a) and (b) are SEM images of PS spheres (200 nm) on the substrate; (c) is the SERS spectra of PS spheres (200 nm) with different concentrations; (d) is the relationship between different PS concentrations and SERS intensity;

[0024] Figure 6In the figure, (a) is the UV-vis diffuse reflectance spectra of Cu2S, MoS2 and Cu2S@MoS2 heterostructures; (b) is the PL spectrum of the substrate; (c) is the EIS Nyquist plot of Cu2S, MoS2 and Cu2S@MoS2 heterostructures; (d) is the photocurrent response of the prepared Cu2S, MoS2 and Cu2S@MoS2 heterostructures in 0.1M Na2SO4 solution under UV-visible light, including on / off cycles; (e) is the comparison of SERS performance of different substrates; (f) is the energy level diagram of the charge transfer process between MB and CF / Cu2S@MoS2 substrate.

[0025] Figure 7 This is the result diagram of Comparative Example 1. DETAILED DESCRIPTION

[0026] Example 1

[0027] Step 1: Preparation of Cu(OH)2 nanorod arrays (CF / Cu(OH)2)

[0028] The CF substrate (copper foam, 2×4cm 2 ) was subjected to a thorough cleaning procedure, including treatment with 3M HCl, deionized water, and anhydrous ethanol, to eliminate surface contaminants. Afterwards, a precursor solution was prepared by dissolving 2.00 g of NaOH and 0.57 g of (NH4)2S2O8 in 20 mL of deionized water, and after complete dissolution, the CF was immersed in the precursor solution for 8 min. Subsequently, the treated CF was extensively rinsed with deionized water and ethanol to remove any residual reactants, and the surface color changed from orange to blue, indicating the formation of Cu(OH)2 nanorods on the CF surface, resulting in a CF / Cu(OH)2 composite.

[0029] Step 2: Synthesis of Cu2S nanorod arrays (CF / Cu2S)

[0030] 0.4 g of Na2S·9H2O was dissolved in 40 mL of deionized water and treated with ultrasound until a clear solution was obtained. The resulting clear solution was then transferred to a polytetrafluoroethylene (PTFE) high-pressure reactor (100 mL capacity). The CF / Cu(OH)2 composite material was introduced into the clear solution and reacted at 100°C for 6 hours. After the reaction was completed, the CF / Cu2S composite material was thoroughly washed with deionized water and anhydrous ethanol, and then dried. The color of CF changed from blue to dark brown and was converted into Cu2S to obtain a CF / Cu2S composite material.

[0031] Step 3: Preparation of CF / Cu2S@MoS2 nanorod arrays

[0032] 11 mg of Na2MoO4·2H2O and 22 mg of (NH2)2CS were dissolved in 20 mL of deionized water, followed by ultrasonic treatment to obtain a clear solution. 2 The CF / Cu2S composites were immersed in this clear solution and heat treated in an oven at 180 °C for 22 h. The obtained CF / Cu2S@MoS2 composites were washed with deionized water and ethanol and then dried at 60 °C for 12 h to ensure the complete removal of any residual solvent.

[0033] Comparative Example 1

[0034] Step 1: Preparation of Cu(OH)2 nanorod arrays (CF / Cu(OH)2)

[0035] CF substrate (copper foam, 2×4cm 2 ) was subjected to a thorough cleaning procedure, including treatment with 3M HCl, deionized water, and anhydrous ethanol, to eliminate surface contaminants. Afterwards, a precursor solution was prepared by dissolving 2.00 g of NaOH and 0.57 g of (NH4)2S2O8 in 20 mL of deionized water, and after complete dissolution, the CF was immersed in the precursor solution for 8 min. Subsequently, the treated CF was extensively rinsed with deionized water and ethanol to remove any residual reactants, and the surface color changed from orange to blue, indicating the formation of Cu(OH)2 nanorods on the CF surface, resulting in a CF / Cu(OH)2 composite.

[0036] Step 2: Preparation of CF / Cu2S@MoS2 nanorod arrays

[0037] 11 mg of Na2MoO4·2H2O and 22 mg of (NH2)2CS were dissolved in 20 mL of deionized water, followed by ultrasonic treatment to obtain a clear solution. 2 The CF / Cu(OH)2 composite was immersed in this clear solution and heat treated in an oven at 180 °C for 22 h. The obtained CF / Cu2S@MoS2 composite was washed with deionized water and ethanol and then dried at 60 °C for 12 h to ensure the complete removal of any residual solvent.

[0038] from Figure 7It can be clearly observed that when the separate sulfurization step in step 2 is omitted, the substrate material undergoes significant changes. The synchronous reaction of thiourea with Na2MoO4 and Cu(OH)2 leads to the simultaneous formation of MoS2 and Cu2S. This results in the local collapse of the Cu(OH)2 nanorods and the disorder of the surface structure. More importantly, the formed MoS2 does not form the expected core-shell structure with Cu2S, but independently forms a MoS2 nanoflower structure. Therefore, two separate structures are observed, rather than a tightly connected heterojunction. In addition, the lack of a uniform and consistent core-shell nanorod array structure further emphasizes the importance of the separate sulfurization step. This step is indispensable for the formation of stable and functional CF / Cu2S@MoS2 core-shell heterostructure nanorod arrays.

[0039] 1. Material Characterization

[0040] The CF / Cu2S@MoS2 composite material obtained in Example 1 was characterized by a variety of analytical techniques. Scanning electron microscopy (SEM) images were obtained on a Gemini500 SEM system. The crystal structure was evaluated using a Cu Kα radiation system. A rotating anode X-ray diffractometer (Rigaku D / Max-γA) was used with data collection ranging from 20° to 80°. Transmission electron microscopy (TEM) characterization and energy dispersive X-ray spectroscopy (EDS) analysis were performed on a JEM 2100F instrument. UV-vis absorption spectra were obtained on a Shimadzu DUV-3700 spectrophotometer. Fluorescence spectra were measured on a Shimadzu Spectrofluorometer FS5. The photoelectrochemical properties of the synthesized materials were characterized by using an electrochemical workstation (CHI660E) with a standard three-electrode configuration. Raman spectra were detected by using a portable Raman instrument (i-Ramanplus, B&W Tek Inc., USA).

[0041] 2. SERS measurement of samples

[0042] To detect model molecules, the prepared substrate was immersed in the analyte solution and kept for 2 hours before Raman analysis to ensure sufficient interaction between the analyte and the substrate surface. For the detection of microplastics, 20 μL of microplastic dispersion was applied to the substrate surface and allowed to dry naturally before collecting SERS signals. SERS spectra were obtained in the range of 400-3000 cm -1The high SERS intensity sites within the range were collected, and each spectrum was collected using a single accumulation of 3 seconds under consistent conditions: laser wavelength of 785nm, laser power of 30mW, and a 50× magnification objective mirror (i-Ramanplus, B&W Tek Inc., USA). Baseline correction was applied to all SERS spectra to minimize environmental interference from stray light.

[0043] The facile and scalable synthesis strategy of CF / Cu2S@MoS2 nanorod arrays mainly includes NaOH etching, Na2S sulfidation, and epitaxial growth of MoS2, e.g. Figure 1 a. The micromorphology of each sample was characterized using scanning electron microscopy. Commercially available copper foam was selected as the SERS substrate due to its high porosity, conductivity, unique 3D structure and mechanical stability. High-density Cu(OH)2 nanorod arrays were in situ grown on the CF surface by an alkaline etching method. Subsequently, the Cu(OH)2 precursor was sulfided by a hydrothermal method to obtain copper sulfide nanorod arrays. Finally, MoS2 nanoparticles were grown directly on the Cu2S nanorods using an in situ growth strategy to form CF / Cu2S@MoS2 nanorod arrays with a core-shell heterostructure. This vertical growth of Cu2S@MoS2 nanorod arrays, as well as the carefully designed core-shell heterostructure, not only enhances mass transport but also ensures efficient electron transfer to the active sites.

[0044] Figure 1 be shows the SEM images of Cu foam, CF / Cu(OH)2; CF / Cu2S; CF / Cu2S@MoS2. SEM analysis shows that the average diameter of the synthesized CF / Cu2S nanorods is about 370nm ( Figure 1 a), which is smaller than the 198 nm diameter of the CF / Cu(OH)2 nanorods ( Figure 1 b) is significantly larger. Subsequently, after in situ growth of MoS2 on CF / Cu2S nanorods, the diameter of CF / Cu2S@MoS2 core-shell nanorods increases to about 566nm ( Figure 1 c). It is noteworthy that the uniformly distributed MoS2 is firmly fixed on the CF / Cu2S nanorods to form a core-shell heterojunction structure. This structure not only enhances the atomic structure and surface properties of the material, but also significantly improves its SERS performance.

[0045] The internal structure of the CF / Cu2S@MoS2 core-shell nanorods of Example 1 was examined using a high-resolution transmission electron microscope. Figure 2In a and 2b, it can be clearly seen that the MoS2 layer is tightly wrapped around the Cu2S nanorods. The observed lattice spacing is 0.226nm and 0.611nm, corresponding to the (103) and (002) crystal planes of MoS2, respectively32, while in Figure 2 In c, the lattice spacing of 0.317 nm is associated with the (-104) plane of Cu2S. The selected area electron diffraction (SAED) pattern shows the (106) crystal plane and the (-104) crystal plane of single-crystalline Cu2S. The above results indicate that a heterostructure is formed within the CF / Cu2S@MoS2 core-shell nanorods. The synthesis of MoS2 was carried out at a relatively low temperature (180°C). This temperature condition affects the formation of a single crystal structure, resulting in dispersed polycrystalline regions observed in the image. Energy dispersive X-ray spectroscopy (EDS) elemental mapping of CF / Cu2S@MoS2 core-shell nanorods ( Figure 2 dg).

[0046] The distribution of Cu, S, and Mo elements is clearly depicted. The composition of the nanorods includes 66.58% Cu, 30.52% S, and 2.9% Mo. The EDS spectrum of Cu2S@MoS2 core-shell nanorods is shown in Figure S2. In addition, the materials were characterized using XRD, as shown in Figure 2 As shown in h, diffraction peaks appear at 48.3°, 45.9°, 37.3° and 27.1°, corresponding to the (106), (630), (034) and (-104) crystal planes of Cu2S, respectively (PDF#33-0490), and diffraction peaks appear at 43.4°, 50.5° and 74.2°, corresponding to the (111), (200) and (220) crystal planes of Cu, respectively (PDF#99-0034). The broad diffraction peaks indicate the nanoscale characteristics of the product, and the XRD pattern is consistent with that of few-layer MoS2. No MoS2 diffraction peaks were observed in the Cu2S@MoS2 composite material because of the low MoS2 content and insufficient crystallinity. Raman spectroscopy is a sensitive method to clearly identify the formation of 1T-MoS2. Figure 2 As shown in i, for 1T-MoS2, J1 (142.8cm -1 )、J2(233.1cm -1 )、E1g(277.7cm -1 ) and J3(333.6cm -1 ) are new and obvious peaks, which are typical vibration modes of 1T-MoS2 34 After MoS2 was composited with Cu2S, the Raman vibration peak of 1T-MoS2 was also obvious. XPS further clarified the composition of the obtained sample. Figure S3 shows the presence of Mo, S, Cu and O in the CF / Cu2S@MoS2 heterojunction. Table S1 gives the peak positions of each component used for peak fitting. Figure 3 As shown in j, for MoS2, four peaks were fitted: 227.3eV (1T-Mo 4+ 3d5 / 2)、232.2eV(1T-Mo 4+ 3d3 / 2), while the peak at 226.2 eV corresponds to S 2s in MoS2, which is consistent with the energy barrier reported in the literature. In addition, the peaks at 161.9 eV and 163.2 eV in the Cu2S@MoS2 sample are consistent with the S 2- In the high-resolution Cu2p spectrum of Figure S3c, the two peaks at 952.1 and 932.2 eV correspond to Cu + The two peaks at 954.2 and 934.4 eV belong to Cu 2p1 / 2 and Cu 2p3 / 2, respectively. 2+ Cu 2p1 / 2 and Cu 2p3 / 2; the swing satellite peaks at 942.6 and 962.2 eV confirm that Cu 2+ The O1s XPS spectrum of Cu2S@MoS2 can be divided into three peaks, corresponding to MoO3 of Mo-O bond, water adsorbed on the surface and -OH species. 18 It can be seen that the presence of oxygen is beneficial to CT resonance.

[0047] 3. In order to explore the effects of different reaction temperatures and different reaction times on the SERS performance of the substrate, in Comparative Examples 1, 2, and 3, the reaction times were 20 h, 24 h, and 26 h, respectively, and the remaining steps were the same as in Example 1; the reaction temperatures of step three in Comparative Examples 4, 5, and 6 were 170°C, 180°C, 190°C, and 200°C, respectively, and the remaining steps were the same as in Example 1.

[0048] Figure 3 ad are the scanning electron microscope images of the corresponding materials at different temperatures, from which it can be clearly seen that as the reaction time increases, the amount of MoS2 increases, the originally clearly visible nanorod array structure becomes only a small part of the protrusion, and the generated MoS2 fills the original existing gaps. Figure 3It can be clearly seen in i and 3j that the SERS performance of the substrate increases first and then decreases as the reaction time increases. As the reaction time increases, more and more MoS2 is generated, so the SERS performance increases; the reason for the decrease is that the thickness of MoS2 increases, and the thickness change of the MoS2 layer on the Cu2S array affects the electron transfer efficiency. The thin MoS2 layer has little effect on the electromagnetic field generated by Cu2S, while the thick MoS2 layer may shield the electromagnetic field and reduce the surface electric field strength, thereby hindering the transfer of electrons from Cu2S to the MoS2-MB interface. Therefore, too much MoS2 will prevent the formation of electromagnetic hotspots; at the same time, the array is also destroyed, which together leads to the weakening of the Raman signal.

[0049] Figure 3 eh correspond to the SEM images at 170°-200°C, where the temperatures of e, f, g, and h are 170°C, 180°C, 190°C, and 200°C, respectively. It can be seen from the figure that most of the MoS2 generated at low temperature is a flocculent material formed by the disorderly accumulation of amorphous MoS2 flakes. As the temperature rises, layered MoS2 is gradually generated. Figure 3 k and Figure 3 l shows the change of SERS performance with temperature. As the temperature increases, the properties of the material first increase and then weaken, which is consistent with the theory. At 170°C, the synthesis of MoS2 decreases, resulting in a decrease in the MoS2 loading on Cu2S and a decrease in SERS performance. When the temperature is higher than 180°C, as the temperature increases, the 1T phase of MoS2 transforms to the 2H phase, resulting in an increase in the proportion of 2H phase MoS2, thereby reducing the SERS activity of the substrate.

[0050] The chemical sensor based on CF / Cu2S@MoS2 matrix was used to detect MB by SERS. The chemical sensor was immersed in 200 μL MB solution of different concentrations for 2 hours. The relationship between the intensity of the MB characteristic band and the initial concentration was shown in the figure below. Figure 4 It is observed that the SERS detection concentration of MB can reach 10 -8 M, the calculated EF value is 4.46×10 6 The Raman characteristic peak of MB is located at 1162cm -1 、1338cm -1 、1403cm -1 and 1617cm -1 , of which 1617cm -1 The strongest peak at 240 nm is derived from the CC ring stretching mode. In addition, other Raman peaks displayed by MB are also associated with specific vibration modes, as shown in Table 1. Figure 4 b shows the MB at 1617 cm -1The calibration curve of the SERS intensity at 100 nm showed a strong linear correlation. The linear regression of the calibration curve resulted in a mathematical model with a correlation coefficient (R2) of 0.94, indicating high linearity over the entire detection range. The long-term stability of the substrate was evaluated by comparing the SERS activity of the freshly prepared substrate with that of the substrate stored in air for 10, 30, and 60 days, respectively. Figure 2 h shows that after 10 days, 30 days and 60 days, 1617 cm -1 The Raman intensity at 400 nm decreased by about 3.6%, 5.7%, and 8.1%, respectively, indicating good stability. Next, the uniformity of the SERS signal was evaluated by collecting spectra from 25 random locations on the substrate ( Figure 4 d). The results show that the substrate has a high signal uniformity, 1617cm -1 The relative standard deviation (RSD) of the peak was 10.3% ( Figure 4 e). The repeatability of five independent batches of experiments was evaluated for this matrix, and the results showed that the RSD values ​​of each batch were 10.5%, 10.3%, 10.7%, 10.6% and 10.5%, respectively, and the RSD value of the whole batch was 10.5% ( Figure 4 f), which confirms the consistency of this matrix across multiple batches of experiments.

[0051] Table 1. The Raman peaks and assignments ofMB molecule.

[0052]

[0053] In order to visualize and quantify the microplastics on the substrate, scanning electron microscopy and Raman spectroscopy were combined to obtain the morphology and chemical composition of the microplastics. Figure 5 As shown in a and 5b, the SEM images show the morphology and size of the 200 nm PS nanospheres adsorbed on the substrate, and the PS spheres are firmly attached to the substrate surface. Figure 5 c and 5d show the SERS spectra of PS nanospheres at different concentrations on the substrate, as well as the linear correlation between concentration and SERS intensity. The data show that the substrate can distinguish trace levels of 50 μg / mL with an R2 of 0.98, indicating that the substrate has an excellent linear fit within the detection range.

[0054] 3.5. Enhancement mechanism of CF / Cu2S@MoS2 nanorod arrays

[0055] The optical properties of the synthesized Cu2S, MoS2 and Cu2S@MoS2 composites were investigated by UV-Vis spectroscopy. Figure 6a). Cu2S, MoS2 and Cu2S@MoS2 composites exhibit comprehensive absorption regions, with significant absorption of light in the range of 400-900nm. This absorption enhancement is attributed to the excellent light absorption ability of Cu2S and MoS2 (narrow bandgap semiconductor materials). Under laser excitation with a wavelength of 785nm, the ground state electrons of n-type MoS2 and p-type Cu2S transition to the conduction band (CB), and the holes remain in the valence band (VB). The electrons in the Cu2S CB are transferred to MoS2 and recombine with the holes in the MoS2 VB. Local charge redistribution occurs near the pn junction interface, resulting in band bending of MoS2 and Cu2S. The built-in electric field enhances the conductivity and leaves holes in the VB. The built-in electric field enhances the conductivity and promotes charge transfer (CT). The CT process follows the semiconductor-molecule CT mechanism. This CT amplifies the polarization tensor of the system, enhances the interaction between molecules and semiconductors at the interface, and thus enhances the intensity of the Raman signal.

[0056] Figure 6 The photoluminescence spectrum in b shows that the peak intensity of the heterojunction structure is the lowest, which reflects the effective separation of photoinduced electron-hole pairs within the heterojunction structure. The photoelectric properties of the samples were also characterized. In order to better demonstrate the charge transport behavior of Cu2S@MoS2, Cu2S, and MoS2, electrochemical impedance spectroscopy (EIS) measurements were performed without photoexcitation ( Figure 6 c). Figure 6 d shows the photocurrent response curves of Cu2S@MoS2, Cu2S, and MoS2. The data show that the photocurrent density of Cu2S@MoS2 is higher, which confirms the enhanced charge transfer and improved charge separation within the heterostructure. Figure 6 e shows the SERS spectra of MB on Cu2S nanorod arrays, MoS2 powder, and the bottom of Cu2S@MoS2 nanorod arrays, respectively. The figure clearly shows that the SERS signal intensity increases significantly after the heterojunction is formed. The Cu2S@MoS2 heterostructure takes advantage of the unique properties of each constituent material to generate a large number of charge carriers, which are effectively separated and transferred. Specifically, Cu2S becomes an electron donor due to its well-arranged energy levels, while MoS2 is conducive to the adsorption and electron transfer of target molecules due to its own characteristics. The synergistic effect in the Cu2S@MoS2 heterostructure not only promotes the separation of photoinduced electron-hole pairs, but also enhances the interfacial charge transfer, thereby improving the SERS performance.

[0057] like Figure 6As shown in f, due to energy limitation, 785nm laser (1.57eV) is sufficient to excite electrons from the VB of Cu2S and MoS2 to the CB of 1.17eV and 1.2eV, respectively, but it is not enough to induce molecular resonance between the HOMO and LUMO levels of MB. During the PICT process of the Cu2S@MoS2-MB system, light usually excites electrons from the VB of Cu2S to its surface states, and then from these surface states to the CB of MoS2. The close combination of these two semiconductors will produce a "level doping" effect between their conduction band and valence band. 41,42 .At the same time, photoinduced charge transfer resonance (μPICT) occurs between MoS2 and MB molecules, which increases the carrier density in the MoS2-MB system through interfacial charge transfer. Therefore, the PICT efficiency within the entire Cu2S@MoS2-MB system is significantly improved, thereby enhancing the SERS activity of the Cu2S@MoS2 heterostructure. In contrast, when the MoS2 layer is too thick, the electrons generated in the core Cu2S cannot reach the MoS2-MB interface.

[0058] Therefore, the present application provides a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate and its preparation method and application. The CF / Cu2S@MoS2 heterostructure substrate exhibits excellent uniformity with an RSD of 10.3%. The CF / Cu2S@MoS2 heterostructure also exhibits excellent performance in detecting microplastics and nanoplastics. The detection limit of PS particles reaches 50μg / mL and shows a strong linear correlation (R 2 =0.98).

[0059] In the description of this specification, the description with reference to the terms "an experimental example", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the experimental example or example are included in at least one experimental example or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same experimental example or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more experimental examples or examples in a suitable manner.

[0060] Finally, it should be noted that the above experimental examples are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred experimental examples, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate, characterized in that: The preparation method of CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate is as follows: Step 1: After cleaning the CF substrate, immerse it in a precursor solution for reaction. After the reaction, rinse the treated CF substrate to obtain a CF / Cu(OH)2 composite material; Step 2, dissolving Na2S·9H2O in deionized water, performing ultrasonic treatment to obtain a clear solution, then adding the CF / Cu(OH)2 composite material obtained in step 1 to the clear solution, transferring the solution to a high-pressure reactor, and after the reaction is completed, washing and drying to obtain a CF / Cu2S composite material; Step 3: prepare a mixed solution, immerse the CF / Cu2S composite material obtained in step 2 into the mixed solution for heat treatment, wash and dry to obtain the CF / Cu2S@MoS2 composite material after the heat treatment.

2. A CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate according to claim 1, characterized in that: In step 1, the CF substrate is cleaned by using HCl, deionized water and anhydrous ethanol in sequence, and the precursor solution is a mixed solution of NaOH solution and (NH4)2S2O8 solution.

3. The CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate according to claim 1, characterized in that: In step 3, the mixed solution is prepared by dissolving Na2MoO4·2H2O and (NH2)2CS in deionized water, and then performing ultrasonic treatment to obtain a mixed solution.

4. The CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate according to claim 3, characterized in that: In step three, the specific steps of heat treatment are: immersing the CF / Cu2S composite material obtained in step two into the mixed solution and placing it in an oven at 180°C for heat treatment for 22 hours.

5. A heterojunction surface enhanced Raman scattering sensing substrate obtained according to the preparation method of a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate according to any one of claims 1 to 4.

6. Application of a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate according to claim 1 in microplastics and nanoplastics.

7. The use of a CF / Cu2S@MoS2 heterojunction surface enhanced Raman scattering sensing substrate in microplastics and nanoplastics according to claim 1, characterized in that: The detection concentration of polystyrene particles by the CF / Cu2S@MoS2 heterojunction surface-enhanced Raman scattering sensing substrate is at least 50 μg / mL, and the minimum detection concentration of methylene blue is 10 -8 M.

Citation Information

Patent Citations

  • Method for carrying out SERS (Surface Enhanced Raman Scattering) detection by taking nano-grade Cu<2-x>S material as substrate

    CN104730056A

  • MoS2@Cu2S@ copper foam composite nanometer material and preparation method and application thereof

    CN108950585A

  • Super-hydrophobic CuO@Ag nanowire array and application thereof in cyclic SERS detection of malachite green

    CN113533297A

  • MoS2 / Cu2S / MoO3 ternary composite material and application thereof in hydrogen evolution and trace detection

    CN116943690A

Cited By

  • Composite SERS (Surface Enhanced Raman Scattering) substrate based on needle tip silicon wafer and preparation method and application thereof

    CN120352408A